EXCELLENT SERVICE IN INCREASING STUDENT SATISFACTION WITH ACADEMIC SERVICES - Abdullah Fikri Sholehuddin SN; Muhammad Fadhli; Yahfizham (Pena Cendekia Insani, 2025)
This study seeks to ascertain the impact of superior service on student satisfaction with academic services, evaluated through five dimensions: physical appearance, responsiveness, reliability, empathy, and assurance. Data collection involved interviews, focus group discussions, observations, and documentation, followed by analysis through data reduction, presentation, and conclusion formulation. The research findings suggest that academic services at FITK UIN SU are typically effective and of excellent quality across all dimensions. Nonetheless, the physical appearance elements remain inadequate, including diminutive projectors, sluggish internet connectivity, inadequate air conditioning, compromised seating, and classroom capacity that fails to accommodate the student population. Nonetheless, the amenities for the postgraduate courses are more sufficient. These findings underscore the necessity for enhancements in buildings and infrastructure to bolster academic services. This research offers both theoretical and practical insights into educational policy, namely in primary services aimed at improving student happiness.